PUBLIC AID AS AN EFFICIENT TOOL FOR DEVELOPING THE RAIL SECTOR IN EU MEMBER STATES: Pomoc publiczna - Postula, Marta; Jarecki , Stefan; Jaworski , Krzysztof (Torun International Studies, 2022)
Rail transport is paramount for the functioning of a sustainable and efficient transport system. EU policy identifying significant role of rail translates into a strong financial support allocated to the transport sector both in the form of services funding and of infrastructure investments. In the study conducted, the impact of public support for rail transport was analyzed in reference to several indicators describing the condition of that sector. The analysis covered an assessment of the impact of public support granted based on PSO – Public Service Obligation, and of the support for infrastructure investments. The results reveal a great variability of the outcome across countries. Countries which provide stronger support for infrastructure investments are characterized, as a rule, by better performance. In the Authors’ opinion, strengthening the support for infrastructure investments at the expense of support granted as part of PSO should be the path for rail funding policy redefinition.